Pengaruh Penerapan E-Billing dan E-Filing Terhadap Kepatuhan Wajib Pajak pada Kantor Pelayanan Pajak Pratama Kramat Jati - Vinti Farida, Wiwin; Subaki, Ahmad; Sumardi, Sumardi (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The purpose of this research is to evaluate how the introduction of the e-filing dan e-billing systems has affected taxpayer compliance at the Kramat Jati Pratama Tax Office. This study uses quantitative techniques and explanatory research. The variables investigated are taxpayer compliance as the dependent variable, and e-filing and e-billing as the independent variables. The Kramat Jati Pratama Tax Office (KPP Pratama) in Jakarta was the subject of this study. The sample selection used accidental sampling, where data collection was carried out unintentionally. The researcher sampled taxpayers she happened to encounter at the Kramat Jati Pratama Tax Office in Jakarta in 2019. Data was collected using a questionnaire. Among the data processing and analysis methodologies employed were data quality testing, multiple linear regression analysis, accounting analysis, hypothesis testing, and classical assumption testing. Data analysis conducted with SPSS version 21. 0 resulted in the formulation of a multiple linear regression equation, expressed as Ŷ = 1. 357 + 0. 316 X1 + 0. 370 X2 + e. This model has undergone evaluations to ensure it meets the criteria for normal distribution, lacks multicollinearity, heteroscedasticity, and autocorrelation, thus being classified as the BLUE (Best Linear Unbiased Estimator) regression model. The test results indicate that the e-billing variable has a significant impact on taxpayer compliance, with a computed t value (3. 652) > t table (1. 66482) at a significance level of 0. 000 <0. 05. With a calculated t value (4. 271) >t table (1. 66482) at a significance level of 0. 000 < 0. 05, the e-filing variable has a significant impact on taxpayer compliance. The outcomes of a multiple linear regression analysis reveal that the Adjusted R2 value is 0. 471, or 47. 1%, and that the taxpayer compliance variable can be explained by the e-billing and e-filing variables, with the remaining 52. 9% (100% - 47. 1%) being attributable to other variables like e-invoice, e-nofa, and e-SPT. With a significance level of 0. 000 <0. 05, the computed F (34. 271) and F (3. 95) were derived using simultaneous hypothesis testing (F-test) in the ANOVA model. As a result, we accept H3, which states that taxpayer compliance is significantly impacted by both e-filing and e-billing at the same time. Future researchers interested in doing research with the same title should examine dependent variables beyond e-billing and e-filing, as well as increase the size of their study samples, according to the aforementioned findings.